Evaluation of Nucleic Acid Amplification Tests as Reference Tests for Chlamydia trachomatis Infections in Asymptomatic Men - Johnson, Robert E. (American Society for Microbiology, 2000)
Urine ligase chain reaction (LCR) and PCR tests and urethral swab culture were compared for their abilities to detect Chlamydia trachomatis infection in 3,639 asymptomatic men by using one-, two-, and three-test reference standards. Frozen urine at four of five participating centers was also tested by a transcription-mediated amplification assay which was used as a reference test. LCR increased the yield of positive results by 27% and PCR increased the yield of positive results by 26% over the yield of positive results by culture (n = 295). LCR and PCR sensitivities were similar, ranging from 80.4 to 93.5%, depending on the reference standard. Culture sensitivity was substantially less. A multiple-test standard yielded LCR, PCR, and culture specificities of 99.6%, with or without discrepant analysis. Test performance varied among centers partly due to different interpretations of the testing protocols. The study confirms that urine LCR and PCR for the detection of C. trachomatis have substantially improved sensitivities over that of urethral swab culture for testing of asymptomatic men, enabling screening of this important target group. These tests, perhaps in combination, are also candidate reference tests for the conduct of test evaluation studies.